An interface heterogeneity study on carbon-based materials using scanning electrochemical microscopy and scanning electrochemical cell microscopy techniques - Al-Lolage, Firas A.; Shafiee, Saiful Arifin (The Korean Electrochemical Society, 2024)
Carbon materials, such as the boron-doped diamond (BDD), are commonly used in the field of electroanalytical sensors and chemical generators. This study focuses on using the scanning electrochemical microscopy (SECM) and the scanning electrochemical cell microscopy (SECCM) techniques for probing the surface heterogeneity of the carbon-based materials of interest. Three BDD electrodes with high concentrations of boron doping, were investigated in this study. The GC and HOPG electrodes were used as standards for their behaviour. The SECM results on the lowest doped BDD electrode (2.94×1020 cm–3; 2000 ppm) in this study imply that the BDD electrode behaves similar to a gold substrate: The feedback kinetic rate constant, kfeedback, obtained, was 0.009–0.013 cm s–1 (the gold substrate’s value: 0.014 cm s–1). The Raman spectra show that all the BDD electrodes exhibit metallic conductivity and also that the non-diamond carbon (NDC) cannot be removed from the BDD films. The presence of graphite, buckminsterfullerene, and fullerite were detected in the BDD films based on the X-Ray diffraction (XRD) spectra. A background current and a potential window study were performed, using the SECCM technique; the BDD electrode with the lowest boron doping shows the widest potential window among the electrodes of interest. This potential window decreases as the boron concentration increases. The results of the standard electrodes show that they share the same and narrowest potential windows among the carbon electrodes. The HOPG electrode has the smallest double layer capacitance while the GC electrode has a relatively large background current. As the boron concentration increases, the background currents for the BDD electrodes increase. The same carbon-based electrodes were also investigated in dissolved ferrocyanide using the SECCM technique. The results show that the GC electrode has the fastest kinetic transfer in comparison to the HOPG electrode. As the boron concentration increases, the kinetic transfer of the BDD electrodes increases.